Servants or subversives thinking Christianly about the Christian presence in the school - Hill, Brian (Sydney, NSW Australian Teachers' Christian Fellowship, 1981)
1980 Includes bibliographical references.
Donated by the Australian Teachers' Christian Fellowship, residents of Emmaus Bible College, March 2004.
Keywords: Teaching -- religious aspects -- Christianity